Improvement of nutritional content of crackers using powdered malunggay (Moringo Oleifera) leaves. - Pelingon, Daisybelle Galve
The study focused on the improvement of crackers with the use of powdered malunggay leaves. Three formulations of crackers with 5%, 10% and 15% malunggay powder, designated as F1, F2, and F3, respectively were prepared and subjected to rank test for preference and general acceptability test (9-point hedonic scale). Kramer?s rank sum test at α = 0.05 revealed that the three formulations were significantly different. Malunggay crackers (with 5% malunggay powder) prepared from F1 was the most preferred formulation. It had significantly higher rating like very much (Kruskal-Wallis Test). Malunggay crackers had significantly lower aw (0.297) than the control (0.335) as revealed by t-test. It had 3.76% moisture content (MC), 15.38% crude fat and 66.67% carbohydrate content which were significantly lower than those of the control with 4.01% MC, 16.31% crude fat and 71.39% carbohydrate (t-test). Whereas, crude protein (9.87%), crude fiber (1.94%) and ash (2.37%) of malunggay were significantly higher than those of the control with 4.88% crude protein, 1.48% crude fiber and 1.93% ash (t-test). Vitamin A and iron content of crackers significantly increased with the addition of malunggay powder (t-test). Malunggay crackers had vitamin A content of crackers significantly increased with the addition of malunggay powder (t-test). Malunggay crackers had vitamin A content of 1806 μg/100g and 0.1716 mg/g iron which were significantly higher than those of the control. Three pieces of malunggay crackers (5g/piece) can meet 90.3% of the RDA of vitamin A and 37% of the RDA of iron for children (1-3 years old). Malunggay crackers, light green, had moderate amount of malunggay powder which were uniformly distributed. It was moderately crunchy, moderately salty with moderate malunggay flavor and odor. It was highly acceptable among children, 65% of rated the product like moderately. Out of 120 respondents, 39% rated the malunggay crackers like very much and 36% like moderately.